Contribution of emotional intelligence towards graduate students' critical thinking disposition - Kang, Fong Luan (Australian International Academic Centre, 2015)
Good critical thinkers possess a core set of cognitive thinking skills, and a disposition towards critical thinking. They are able to think critically to solve complex, real-world problems effectively. Although personal emotion is important in critical thinking, it is often a neglected issue. The emotional intelligence in this study concerns our sensitivity to and artful handling of our own and others’ emotions. Engaging students emotionally is the key to strengthening their dispositions toward critical thinking. Hence, a study involving 338 male and female graduate students from a public university was carried out. They rated the Emotional Intelligence Scale and Critical Thinking Disposition Scale. Findings suggested that emotional intelligence and critical thinking disposition were positively correlated (r=.609). Differences in terms of age, gender, and course of study also formed part of the analysis.